Respiratory Tract Microecology and Bronchopulmonary Dysplasia in Preterm Infants - Tong Sun; Haiyang Yu; Jianhua Fu (Frontiers Media S.A., 2021)
Bronchopulmonary dysplasia (BPD) is a severe respiratory complication in preterm infants. Although the etiology and pathogenesis of BPD are complex and remain to be clarified, recent studies have reported a certain correlation between the microecological environment of the respiratory tract and BPD. Changes in respiratory tract microecology, such as abnormal microbial diversity and altered evolutional patterns, are observed prior to the development of BPD in premature infants. Therefore, research on the colonization and evolution of neonatal respiratory tract microecology and its relationship with BPD is expected to provide new ideas for its prevention and treatment. In this paper, we review microecological changes in the respiratory tract and the mechanisms by which they can lead to BPD in preterm infants.